EXPERIMENTAL DETERMINATION OF TRACE-ELEMENT PARTITIONING BETWEEN PARGASITE AND A SYNTHETIC HYDROUS ANDESITIC MELT - Brenan J.M.; Shaw H.F.; Ryerson F.J.; Phinney D.L. (My University, 1995)
In order to more fully establish a basis for quantifying the role of amphibole in trace-element fractionation processes, we have measured pargasite/silicate melt partitioning of a variety of trace elements (Rb, Ba, Nb, Ta, Hf, Zr, Ce, Nd, Sm, Yb), including the first published values for U, Th and Pb. Experiments conducted at 1000°C and 1.5 GPa yielded large crystals free of compositional zoning. Partition coefficients were found to be constant at total concentrations ranging from # 1 to > 100 ppm, indicating Henry's Law is operative over this interval. Comparison of partition coefficients measured in this study with previous determinations yields good agreement for similar compositions at comparable pressure and temperature.The compatibility of U, Th and Pb in amphibole decreases in the order Pb > Th > U. Partial melting or fractional crystallization of amphibole-bearing assemblages will therefore result in the generation of excesses in 238U activity relative to 230Th, similar in magnitude to that produced by clinopyroxene. The compatibility of Pb in amphibole relative to U or Th indicates that melt generation in the presence of residual amphibole will result in the long-term enrichment in Pb relative to U or Th in the residue. This process is therefore incapable of producing the depletion in Pb relative to U or Th inferred from the Pb isotopic composition of MORB and OIB.Comparison of partition coefficients measured in this study with previous values for clinopyroxene allows some distinction to be made between expected trace-element fractionations produced during dry (cpx present) and wet (cpx + amphibole present) melting. Rb, Ba, Nb and Ta are dramatically less compatible in clinopyroxene than in amphibole, whereas Th, U, Hf and Zr have similar compatibilities in both phases. Interelement fractionations, such asDNb /DBa are also different for clinopyroxene and amphibole. Changes in certain ratios, such as Ba, Ba, andNb within comagmatic suites may therefore offer a means to discern the loss of amphibole from the melting assemblage.Elastic strain theory is applied to the partitioning data after the approaches of Beattie and Blundy and Wood and is used to predict amphibole/melt partition coefficients at conditions of P, T and composition other than those employed in this study. Given values of DCa, DTi and DK from previous partitioning studies, this approach yields amphibole/melt trace-element partition coefficients that reproduce measured values from the literature to within 40-45%. This degree of reproducibility is considered reasonable given that model parameters are derived from partitioning relations involving iron-and potassium-free amphibole.